Confounding factors in interpreting fracture frequencies in skeletal populations - Lukáš Friedl (AntropoWebzin)
The lifestyle of past populations can be reconstructed with help of several skeletal indicators. One such indicator is trauma. Trauma can be used for inferring about daily activities, subsistence strategy, division of labor, occupational hazards as well as warfare. Paleoepidemiology aimed at the evaluation of pathologies in populations provides a tool, however, since the tool is inferential and the living population does not exist anymore, it also brings some problems in the interpretation. This paper discusses these problem areas on a specific example of fracture frequency interpretations in skeletal populations. There are two main sources of interpretation confusion: methods and biology. Methodological problems are preservation, estimates of number of individuals, age, and sex, fracture recognition and diagnosis, and chronology of burial sites. Biological problems arise from processes of senescence, healing, and bone remodeling.